Is training age predictive of physiological performance changes in developmental rugby league players? A prospective longitudinal study - Booth, M.; Cobley, S.; Halaki, M.; Orr, R. (International Journal of Sports Science & Coaching, 2020)
The aim of this study was to determine if training age - rugby league training age, resistance training age and cardiovascular training age - was predictive of changes in physiological performance in developmental rugby league players. Developmental rugby league players from one elite club (n = 147, mean age = 15.8 ± 1.1 years) playing at Under 16 and Under 18 representative levels were tracked longitudinally over two consecutive seasons. Estimated aerobic capacity, jump height, upper body strength endurance and change of direction were assessed. Mixed method random effect analysis determined relationships between training age domains and physiological change. Positive relationships were observed between rugby league training age and change in estimated V O2max (ß = 0.13, p = 0.018), and change in strength endurance (ß = 0.51, p = 0.033), and resistance training age and change in jump height (ß = 0.11, p = 0.007). A negative relationship was observed between rugby league training age with change in change of direction time (ß = -0.06, p = 0.026). Moderate pre-season training effect sizes were identified for change of direction (effect size = -0.42, confidence interval (CI) = -0.8 to 0.1) and jump height (effect size = 0.41, CI = 0.1-0.7), while small pre-season training effect size was apparent for strength endurance (effect size = 0.33, CI = 0.0-0.7) and estimated V O2max (effect size = 0.16). Small in-season performance decrements occurred in strength endurance (effect size = -0.23, CI = -0.6 to 0.1) and change of direction (effect size = 0.30, CI = -0.1 to 0.7). Higher pre-study rugby league training age was associated with greater improvements in estimated V O2max, strength endurance and change of direction. Additionally, higher resistance training age was associated with greater improvements in vertical jump. Overall, the magnitude of resistance training age and cardiovascular training age may have been too inadequate to meaningfully impact training adaptations in the population. Decrease in effect size for physiological performance changes during the in-season phase suggests that performance enhancements were not maintained across the competitive season.